The McGraw-Hill Civil Engineering PE Exam Depth Guide : Structural Engineering - LWIN, M. Myint (McGraw - Hill Book Company, 2001)
The McGraw-Hill Civil Engineering PE Exam Depth Guide : Structural Engineering